Dysuria Following Stereotactic Body Radiation Therapy for Prostate Cancer - Janowski, Einsley-Marie; Kole, Thomas P.; Chen, Leonard N.; Kim, Joy S.; Yung, Thomas M.; Collins, Brian Timothy; Suy, Simeng; Lynch, John H.; Dritschilo, Anatoly; Collins, Sean P. (Frontiers in Oncology, 2015)
Background Dysuria following prostate radiation therapy is a common toxicity that adversely affects patients’ quality of life and may be difficult to manage. Methods Two hundred four patients treated with stereotactic body radiation therapy (SBRT) from 2007 to 2010 for localized prostate carcinoma with a minimum follow-up of 3 years were included in this retrospective review of prospectively collected data. All patients were treated to 35–36.25 Gy in five fractions delivered with robotic SBRT with real time fiducial tracking. Dysuria and other lower urinary tract symptoms were assessed via Question 4b (Pain or burning on urination) of the expanded prostate index composite-26 and the American Urological Association (AUA) Symptom Score at baseline and at routine follow-up. Results Two hundred four patients (82 low-, 105 intermediate-, and 17 high-risk according to the D’Amico classification) at a median age of 69 years (range 48–91) received SBRT for their localized prostate cancer with a median follow-up of 47 months. Bother associated with dysuria significantly increased from a baseline of 12% to a maximum of 43% at 1 month (p < 0.0001). There were two distinct peaks of moderate to severe dysuria bother at 1 month and at 6–12 months, with 9% of patients experiencing a late transient dysuria flare. While a low level of dysuria was seen through the first 2 years of follow-up, it returned to below baseline by 2 years (p = 0.91). The median baseline AUA score of 7.5 significantly increased to 11 at 1 month (p < 0.0001) and returned to 7 at 3 months (p = 0.54). Patients with dysuria had a statistically higher AUA score at baseline and at all follow-ups up to 30 months. Dysuria significantly correlated with dose and AUA score on multivariate analysis. Frequency and strain significantly correlated with dysuria on stepwise multivariate analysis. Conclusion The rate and severity of dysuria following SBRT is comparable to patients treated with other radiation modalities.